Optimization of the osmotic dehydration process for improving the quality of vacuum-fried “Vinh Chau” shallots at the pilot stage [pdf] - Ngô Văn Tài; Nguyễn Minh Thủy (Acta Scientiarum Polonorum Technologia Alimentaria, 2023)
In recent years, particularly during the Covid-19 pandemic, food with high biological activities, which might help to enhance the immune system and reduce the risk of disorders, has attracted public attention (Bellavite and Donzelli, 2020).The onion (Allium ascalonicum) is one such plant with high antioxidant compounds, including phenolics, flavonoids, kaempferols, and quercetin (Thuy et al., 2020).These compounds have health benefits, such as preventing cancer, anti-microbiological activities, strengthening cardiovascular health, reducing high blood pressure and insulin resistance, controlling weight, antioxidant activity, and fighting chronic bronchitis, infections, and fever (Donno et al., 2019;Paczkowska-Walendowska et al., 2021).However, in Vietnam, the shallot is not used effectively, and the price of these materials
Keywords: Garlic and Onion Studies